Quantized field with excitations of spacetime - Hou Yau (Scientific Reports)
Abstract We study a quantized field that can excite its underlying spacetime and has the properties of a bosonic field. A particle in this field is a harmonic oscillator in time, also known as a proper time oscillator, which is an excitation of spacetime. Time in this oscillator flows only forward but with varying rates. In separate analyses, by assuming the same proper time oscillator as a classical object that can remain stationary in space, we show that the spacetime outside is a Schwarzschild field. A classical proper time oscillator mimics the effects of a point mass in general relativity. As shown, a proper time oscillator has the properties of a quantum particle and can act as a gravitational source. Based on these results, if a real particle is an excitation of the corresponding quantum field and its underlying spacetime, the proper time oscillation will allow a real particle to interact directly with spacetime, generating a gravitational field.